75.4k views
1 vote
Identify the correct steps involved in proving that if A, B, and C are sets, then |A ∪ B ∪ C| = |A| + |B| + |C| − |A ∩ B| − |A ∩ C| − |B ∩ C| + |A ∩ B ∩ C|.

User Alex Stiff
by
5.7k points

2 Answers

3 votes

Answer: The step-by-step proof is shown below.

Explanation:

To prove this, we need to first show that

|A U B| = |A| + |B| - |A n B|

Suppose A' and B' are the compliments of A and B respectively.

In a Venn diagram where set A and B intersects, we can see that

B = A' n B

So

|A U B| = |A U (A' n B)|

Where A and A' n B are mutually disjoint.

|A U B| = |A| U |A' n B|

= |A| + |A' U B|

= |A| + |B| - |A n B| (equation 1)

Now, to the main business.

Rewrite A U B U C to look like what we have proven above.

A U B U C = A U (B U C)

All we now have to do is prove for |A U (B U C)|

Easily from (equation 1)

|A U (B U C)| = |A| + |B U C| - |A n (B U C)|

= |A| + [|B| + |C| - |B n C|] - [(A n B) U (A n C)]

= |A| + [|B| + |C| - |B n C|] - [|A n B| + |A n C| - |(A n B) n (A n C)]|

= |A| + |B| + |C| - |B n C| - |A n B| - |A n C| + |A n B n C|

Because

(A n B) n (A n C) = A n B n C

Hence, the proof.

|A U (B U C)| = |A| + |B| + |C| - |B n C| - |A n B| - |A n C| + |A n B n C|

User Aogan
by
6.0k points
5 votes

Answer:

proved.

Explanation:

The detailed steps and appropriate values, elements of each sets were assumed to proved that the LHS is equal to the RHS as shown in the attached file.

Identify the correct steps involved in proving that if A, B, and C are sets, then-example-1